Work Motivation, Career Prospects, and Employment Decisions among Alfa Class Graduates: Intention and Digital Readiness - Diva Azahra; M. Fathur Rahman (JPI: Jurnal Pustaka Indonesia, 2026)
This study examined the influence of work motivation and perceived career prospects on employment decisions among Alfa Class graduates at SMK Negeri 9 Semarang, with employment intention as a mediating variable and digital readiness as a moderating variable. A quantitative explanatory design was employed using a survey method. The respondents consisted of 107 Alfa Class graduates from the 2023–2025 cohorts, selected through a census sampling technique. The research instrument was pilot-tested on 39 Alfa Class graduates at SMK Negeri 1 Kendal, and the main data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings showed that work motivation did not have a significant effect on either employment intention or employment decision. In contrast, perceived career prospects had a strong and significant effect on employment intention (β = 0.589; p < 0.001), while employment intention significantly influenced employment decision (β = 0.584; p < 0.001). Employment intention fully mediated the relationship between perceived career prospects and employment decision, indicating that graduates’s perceptions of career opportunities are translated into employment decisions primarily through the formation of work intention. Digital readiness also had a significant direct effect on employment decision (β = 0.205; p = 0.024), but it did not significantly moderate the relationships among the proposed variables. These findings imply that industry-based vocational programs should not only provide recruitment pathways, but also strengthen students’ perceptions of career prospects, employment intention, and digital readiness to support more effective school-to-work transitions.